Relasi Antar Aktor Dalam Upaya Pemenuhan Kebijakan Energi Baru Terbarukan Di Provinsi Bali Tahun 2019 - Wiswadhipa, Anak Agung Gde Prana; Azhar, MuhammadxAli; Putri Wirantari, I Dewa Ayu (Jurnal Nawala Politika, 2021)
ABSTRACT Thisxstudyxaims toxfind out how the policyxmaking process that involves many parties to carry out a collaborative mechanism that forms relationships between politics actors in the effort to fulfill the renewable energy policy inxBali onx2019th. This study using the Policy Windows theory by John Kingdon as a formulation of the policy agenda of the problems in this study. Thexresearch methodxused in this research is axdescriptive qualitative,which is more concerned about the characteristics, xquality,xnterrelationships of activities in relation to politicsxactors and relations in the fulfillment ofx2019 renewable energy policies. Results of This research is: energy problems in the Province of Bali, which if the agenda setting through cooperation (actorxrelations) to give birth to several MoUs that become the reference for the Government ofxBali Province in formulating policies in the form GovernorxRegulation no.45 about cleanxenergy and encourage the legislature to immediatelyxdraft about clean energyxpolicy. Keywords: ActorxRelations,Renewable Energy, Policy Windows